2018
DOI: 10.1093/chromsci/bmy056
|View full text |Cite
|
Sign up to set email alerts
|

A Needle Trap Device Packed with Nanoporous Silica Sorbents for Separation and Gas Chromatographic Determination of Polycyclic Aromatic Hydrocarbons in Contaminated Soils

Abstract: SBA-15 and MCM-41 nanoporous silica sorbents were synthesized and functionalized by amine groups and used, for the first time, for packing a needle trap device (NTD). The characteristics of the synthesized SBA-15 and MCM-41 sorbents were investigated by X-ray diffraction, scanning electron microscopy and Fourier transfer infrared spectroscopy. The NTD coupling to gas chromatography with a flame ionization detector (GC-FID) was carried out to extract and determine polycyclic aromatic hydrocarbons (PAHs) in cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In the NTME technique, commercial sorbents such as PDMS-DVB, Carboxen, Carbopack X, Tenax TA, and polymer-based beads are used to sample organic compounds from different media. Recently, Mieth et al [87] showed that a combination of different sorbents into the same needle trap could enhance the extraction performance, while Maleki et al [88] customized the NTME with nanoporous silica sorbents, showing the possible wide range of applications for this technique.…”
Section: Nonexhaustive Microextraction Techniquesmentioning
confidence: 99%
“…In the NTME technique, commercial sorbents such as PDMS-DVB, Carboxen, Carbopack X, Tenax TA, and polymer-based beads are used to sample organic compounds from different media. Recently, Mieth et al [87] showed that a combination of different sorbents into the same needle trap could enhance the extraction performance, while Maleki et al [88] customized the NTME with nanoporous silica sorbents, showing the possible wide range of applications for this technique.…”
Section: Nonexhaustive Microextraction Techniquesmentioning
confidence: 99%
“…For fine particle-based methods, various types of containers have been proposed for the microcolumn such as a pipette tip [29], nozzle of a disposable syringe [30], syringe [31], and 21-gauge stainless steel needle [32]. In microcolumn techniques, repeated aspirating/dispensing cycles of the sample solution and eluent are necessary to attain adsorption or desorption equilibria.…”
mentioning
confidence: 99%